Congenital Torsion of a Herniated Accessory Liver Lobe in a Lamb - ahromi, Alireza Raayat; Kamali, Younes; Ahmadi, Nasrollah; Savadkoohi, Hesam (Brazilian Journal of Veterinary Pathology, 2015)
Accessory liver lobe (ALL) is an extremely rare anomaly, which can potentially undergo torsion and ischemia. A case with a herniated and twisted ALL originating from the umbilical fissure in conjunction with liver proper and lung abnormalities in a 2-day-old lamb is presented. The primitive presentation of the case was umbilical hernia that underwent herniorrhaphy and expired because of multiple anomalies. ALL seems to be caused by extra-embryonic entrapment of a portion of the liver as a result of high intra-abdominal pressure.